PENGARUH KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP PERILAKU PENGHINDARAN PAJAK (TAX AVOIDANCE) - ZIDNY NAFI' HASBI; Nur Fitriyanto (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
This study aims to analyze the effect of audit quality proxied by the size of the auditor and audit tenure, while the audit committee proxied by the number and composition of audit committee competency expertise on tax avoidance behavior calculated by the Cash ETR (CETR) method. The population used is companies registered in the Jakarta Islamic Index (JII) in 2015 to 2019, using purposive sampling technique, 11 companies with 55 observations were obtained. This study uses panel data regression, with the best approach after testing the fixed effect model. The results of this study reveal that audit tenure has a positive effect on tax avoidance behavior and the number of audit committees has a significant negative effect on tax avoidance behavior, while auditor size and accounting background have no significant effect on tax avoidance behavior.